PENGARUH KOMITMEN ORGANISASIONAL TERHADAP PRESTASI KERJA KARYAWAN PADA PT. PERMODALAN NASIONAL MADANI (PERSERO) CABANG MANADO - Sengkeh, Devi; Rumawas, W.; Tumbel, Tinneke M. (Sam Ratulangi University, 2017)
The background of this research indicates that the low organizationalcommitment of employees affects that the low performance of work, so theproblem studied in this research is: How big influence OrganizationalCommitment to Employee Work Achievement at PT. Permodalan NasionalMadani (Persero) Branch ManadoEmployee commitment to the organizationshown by employee characteristics is (1) employees are more concerned withpersonal interests than the company's interest in completing the target work,where employees are more focused on personal issues. (2) less maximize thecontribution of his work as part of the organization as a whole in carrying outits duties and obligations; (3) lackof cooperation among employees in solvingthe problem. This shows that the low organizational commitment of employeesresulted in the likelihood of job performance at PT. Permodalan NasionalMadani (Persero) Branch Manado, so the higher one's commitment to the taskthe higher the performance will be generated. In this research the method usedis quantitative method, by using correlation analysis approach and simple linearregression with data analysis technique used is Pearson Product MomentCorrelation Analysis (PPM). Based on the calculation of Pearson ProductMoment correlation, organizational commitment contributed 97.6% while theremaining 2.4% was a contribution from other variables. And there is asignificant influence between Organizational Commitment to EmployeePerformance at PT. Permodalan Nasional Madani (Persero) Branch Manado.While the calculation results of simple linear regression analysis with the resultfhitung â‰¥ ftabel, or 2787.82 â‰¥ 2.05, thus reject Ho, which means a significanteffect. This means that Organizational Commitment has a significant andlinearly influence on Employee Work Performance at PT. PermodalanNasional Madani (Persero) Branch Manado. There is a significant influencebetween organizational commitment employees affect the performance of workat PT. Permodalan Nasional Madani (Persero) Branch Manado. It isrecommended to always pay attention to employee performance for theeffectiveness and efficiency of PT. Permodalan Nasional Madani (Persero)Manado Branch, so as to maintain its reputation as one of the reliable and trustworthy capital business entities.Keywords : Organizational Commitment, Employee Performance.